Luminescence and density banding patterns in massive Porites corals around the Thai‐Malay Peninsula, Southeast Asia. (8th July 2016) - Tanzil, J. T. I.; Lee, J. N.; Brown, B. E.; Quax, Rick; Kaandorp, J. A.; Lough, J. M.; Todd, P. A.
Abstract: We characterized the annual luminescent and skeletal density banding patterns in 51 massive Porites corals from 15 reefs from six locations around the Thai‐Malay Peninsula in Southeast Asia, and explored the seasonal environmental cues/drivers of band formation. Location‐specific recurrent annual luminescent banding patterns were found at all study locations with a brighter band occurring toward the end of the year (∼October/November/December) (at five locations) and in ∼June (one location). Annual density banding patterns could only be discerned at four locations, and were categorized into those that formed a dense band commencing ∼November/December, and those starting ∼May/June. Overall, compared to luminescence, variations in skeletal density provided a less clear signal for demarcation of annual growth increments. Seasonal variations in luminescence showed clearest relationships with salinity, as a proxy for freshwater/river runoff. No convincing relationship between intra‐annual luminescence intensity and density variations was found, which supports the notion that luminescent banding is due to inclusions of fluorophores into the coral skeleton rather than variations in skeletal architecture. The relationships between seasonal density variations and significant wave height and rainfall suggest density banding in this region is likely related to wave energy, or some other correlated environmental parameter/s. The large variability in skeletal banding patterns not only highlights the current relatively poor understanding of their nature and causes, but also the need for replication in their interpretation, especially in settings with complex seasonal hydrodynamic/hydrological patterns such as those found around the Thai‐Malay Peninsula.